The scope and consequences of metaphoric thinking Using individual differences in metaphor usage to understand how metaphor functions. [article]. - Fetterman, Adam K.
People often think, feel, and behave metaphorically according to conceptual metaphor theory. There are normative sources of support for this theory, but individual differences have received scant attention. This is surprising because people are likely to differ in the frequency with which they use metaphors and, therefore, the frequency with which they experience the costs and benefits of metaphoric thinking. To investigate these ideas, a 5-study program of research (total N = 532) was conducted. Study 1 developed and validated a Metaphor Usage Measure (MUM), finding that people were fairly consistent in their tendencies toward literal thought and language on the one hand versus metaphoric thought and language on the other. These differences were, in turn, consequential. Although metaphor usage predicted susceptibility to metaphor transfer effects (Studies 2 and 3), it was also linked to higher levels of emotional understanding (Studies 4 and 5). The findings provide support for several key premises of conceptual metaphor theory in the context of a new measure that can be used to track the consequences of metaphoric thinking. -- (from the authors)